An integrated restoration framework for coverage and communication within wireless sensor networks. (20th March 2014) - Habib, Sami J.; Marimuthu, Paulvanna Nayaki
The paper presents a novel integrated framework to restore the coverage and communication failures within a wireless sensor network (WSN) without adding new resources. We view WSN as a collection of tree topologies, where each tree comprises of base station (BS) as a root, and the sensors as rest of nodes. The sensor/BS failures produce a disjoint set of sensors, thus generating coverage and communication issues simultaneously. We have formulated the restoration within WSN as an optimisation problem, where the objective function is to maximise the lifespan of WSN, subject to energy constraints. The restoration framework employs Simulated Annealing to select the best alternate neighbouring sensor/BS to restore the coverage and communication. The simulation results of a typical WSN with 26% sensor failures and 40% BS failures demonstrate the capability of our framework to maintain 100% communications for up to 200 days of operation than without utilising restoration.